Alteration of the gut microbiota following SARS-CoV-2 infection correlates with disease severity in hamsters. (31st December 2022) - Sencio, Valentin; Machelart, Arnaud; Robil, Cyril; Benech, Nicolas; Hoffmann, Eik; Galbert, Chloé; Deryuter, Lucie; Heumel, Séverine; Hantute-Ghesquier, Aline; Flourens, Anne; Brodin, Priscille; Infanti, Fabrice; et al.
ABSTRACT: Mounting evidence suggests that the gut-to-lung axis is critical during respiratory viral infections. We herein hypothesized that disruption of gut homeostasis during severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may associate with early disease outcomes. To address this question, we took advantage of the Syrian hamster model. Our data confirmed that this model recapitulates some hallmark features of the human disease in the lungs. We further showed that SARS-CoV-2 infection associated with mild intestinal inflammation, relative alteration in intestinal barrier property and liver inflammation and altered lipid metabolism. These changes occurred concomitantly with an alteration of the gut microbiota composition over the course of infection, notably characterized by a higher relative abundance of deleterious bacterial taxa such as Enterobacteriaceae and Desulfovibrionaceae. Conversely, several members of the Ruminococcaceae and Lachnospiraceae families, including bacteria known to produce the fermentative products short-chain fatty acids (SCFAs), had a reduced relative proportion compared to non-infected controls. Accordingly, infection led to a transient decrease in systemic SCFA amounts. SCFA supplementation during infection had no effect on clinical and inflammatory parameters. Lastly, a strong correlation between some gut microbiota taxa and clinical and inflammation indices of SARS-CoV-2 infection severity was evidenced. Collectively, alteration of the gut microbiota correlates with disease severity in hamsters making this experimental model valuable for the design of interventional, gut microbiota-targeted, approaches for the control of COVID-19. Abbreviations: SARS-CoV-2, severe acute respiratory syndrome coronavirus 2; COVID-19, coronavirus disease 2019; SCFAs, short-chain fatty acids; dpi, day post-infection; RT-PCR, reverse transcription polymerase chain reaction; IL, interleukin. ACE2, angiotensin converting enzyme 2; TMPRSS2, transmembrane serine protease 2.